2022
DOI: 10.5897/jphe2022.1410
|View full text |Cite
|
Sign up to set email alerts
|

Perception on cervical cancer and enhancing strategies to screening uptake among women in Bamenda, Cameroon: A qualitative method

Abstract: The treatment of cervical cancer has a good prognosis if diagnosed early. Hence, screening is very vital. The aim of this study was to evaluate the perception of women on cervical cancer and strategies to enhance its screening uptake in the city of Bamenda, Cameroon. Qualitative study was carried out from July, 2019 to August, 2019. Eight focus group discussions were organized in five different quarters in the city of Bamenda. These quarters and participants were purposively selected and each group constituted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
1
1
0
Order By: Relevance
“…This study revealed that the awareness level regarding cervical cancer and its screening among the study participants was low. This finding is in agreement with study findings conducted in Ethiopia 20 , 31 , 41 and other African countries such as Cameroon, 42 Sudan, 43 Uganda, 38 and Malawi. 44 It is also supported by a systematic review of studies from LMICs 45 and a study conducted among ethnic minorities in the UK.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…This study revealed that the awareness level regarding cervical cancer and its screening among the study participants was low. This finding is in agreement with study findings conducted in Ethiopia 20 , 31 , 41 and other African countries such as Cameroon, 42 Sudan, 43 Uganda, 38 and Malawi. 44 It is also supported by a systematic review of studies from LMICs 45 and a study conducted among ethnic minorities in the UK.…”
Section: Discussionsupporting
confidence: 93%
“… 34 Studies from Uganda implicitly reported organisational and health system challenges as a barrier to cervical screening. 37 , 38 Financial constraint is also among the perceived barriers to screening as supported by findings from Arba Minch, Ethiopia, 22 Kenya, 36 , 49 Cameroon, 42 and Uganda. 37 , 38 In Malawi, lack of equipment and supplies and supportive supervision hindered the use of cervical screening.…”
Section: Discussionmentioning
confidence: 75%